The impact of varied fertilisation on the concentration of cadmium and copper in organs of willow trees (Salix viminalis) = Wpływ zróżnicowanego nawożenia na zawartość kadmu i miedzi w wierzbie wiciowej - Sieciechowicz, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the impact of varied fertilisation with sewage sludge on the concentration of cadmium and copper in willow organs during the first three years of cultivation. The lowest mean concentration of cadmium in Salix viminalis biomass was found in the plantation fertilised only with mineral fertilisers
Keywords: kadm; miedź; metale ciężkie; osady ściekowe; Salix viminalis; cadmium; cooper; heavy metals; sewage sludge